2011
DOI: 10.1136/gut.2010.223263
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of the faecal microbiota in patients with Crohn's disease and their unaffected relatives

Abstract: Unaffected relatives of patients with CD have a different composition of their microbiota compared with healthy controls. This dysbiosis is not characterised by lack of butyrate producing-bacteria as observed in CD but suggests a role for microorganisms with mucin degradation capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
668
5
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 921 publications
(720 citation statements)
references
References 47 publications
38
668
5
9
Order By: Relevance
“…Recent studies found that the occurrence of CD is always following a decrease in obligate anaerobes of the phylum Firmicutes and an increase in facultative anaerobes, including members of the family Enterobacteriaceae (Willing et al, 2009(Willing et al, , 2010Joossens et al, 2011). The shift of bacterial communities from obligate to facultative anaerobes strongly suggests a disruption in anaerobiosis and points to a potential role for oxygen in intestinal dysbiosis (Rigottier-Gois 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies found that the occurrence of CD is always following a decrease in obligate anaerobes of the phylum Firmicutes and an increase in facultative anaerobes, including members of the family Enterobacteriaceae (Willing et al, 2009(Willing et al, , 2010Joossens et al, 2011). The shift of bacterial communities from obligate to facultative anaerobes strongly suggests a disruption in anaerobiosis and points to a potential role for oxygen in intestinal dysbiosis (Rigottier-Gois 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that F. prausnitzii (generalist OTU1457) was negatively correlated to and significantly (P ¼ 0.004) much more abundant than B. coprophilus (generalist OTU1517) (Module A in Figures 5b and c), suggesting there may be colonization resistance between F. prausnitzii and B. coprophilus along the length of the intestinal tract. Accordingly, if the turnover of colonization resistance between those two species occurred, the overgrowth of B. coprophilus along the intestine may result in a decrease of F. prausnitzii possibly linked with the presence of gut dysbiosis, such as CD (Willing et al, 2010;Joossens et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysbiosis of intestinal microbiota occurs in ulcerative colitis, irritable bowel syndrome and colon cancer (Moore & Moore, 1995;Flint et al, 2007;Flint & Wallace, 2010;Noor et al, 2010;Sekirov et al, 2010). In a recent cohort study, the microbial community of patients with Crohn's disease was found to be markedly different from healthy controls and their unaffected relatives (Joossens et al, 2011). Density gradient gel electrophoresis (DGGE) of ribosomal PCR amplicons indicated that numbers of Faecalibacterium prausnitzii and Bifidobacterium IP: 34.212.246.108…”
Section: Introductionmentioning
confidence: 99%
“…De manière concomitante, la quantité de certaines bactéries du phylum des Bactéroïdètes augmente fréquemment chez ces patients, qui sont colonisés égale-ment par certaines entérobactéries adhérentes invasives [21]. Une dysbiose est également observée chez les parents au premier degré des patients atteints de la maladie de Crohn [22]. NOD2, un modulateur de la réponse inflammatoire de la muqueuse intestinale C'est dans ce contexte qu'un risque de dysbiose a été révélé chez les souris transgéniques déficientes pour le gène Nod2 (nucleotide-binding oligomerization domain containing 2), mais également chez les patients porteurs de mutations de ce gène majeur de pré-disposition à la maladie de Crohn [23].…”
unclassified